The The Mediating Effect of Disaster Recovery Plan on the Relationship Between Critical Personnel And Business Continuity Management - Naser, Almansoori Fahed Ali; Nor, Azrin (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
The aim of this paper is to investigate the mediating effect of disaster recovery plan on the relationship between critical personnel and business continuity management. The study applied cross sectional quantitative survey approach to collect data using 326 questionnaire from Abu Dhabi municipalities employees. 281 responses were retrieved and analysed for descriptive and inferential statistics. The result shows that the relationship between critical personnel and BCM, as well as critical personnel and DRP were negative. But the DRP -> BCM relationship was found to be positively significant. However, the mediating effect of DRP on critical personnel and BCM relationship was negatively significant against the positive significant mediation posited in the study. Implications, limitations and future study areas have been illustrated in the study.